Genotyping of Newcastle Disease Virus from Feral Birds in Namakkal - Ponnusamy, Suresh; Kuppanan, Sukumar; Ardhanary, Thangavelu (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
In recent days there has been a remarkable increase in the wild bird population closer to intensive poultry rearing area in Namakkal  district. Newcastle Disease (ND) has been reported in more than two hundred species of birds. Among the feral birds, Peafowl (Pavo  cristatus) and Cattle egrets (Bubulcus ibis) are thickly populated in Namakkal district, the second-largest egg-producing belt in India. A  total of 62 fecal samples from peafowls and 40 fecal samples from cattle egrets were collected in and around Namakkal district adjacent  to poultry farms and bodies of water. Samples were processed and inoculated into 9-day-old embryonated chicken eggs through the  allantoic sac for virus isolation. Positive samples which demonstrated hemagglutination activity were subjected to the neutralization  of haemagglutination using standard Newcastle disease serum and confirmation by reverse transcriptase-polymerase chain reaction  (RT-PCR). Out of 62 samples collected from peafowls, none were found to be positive for NDV, and two isolates, namely Cattle Egret/ India/TN-01/2020 and Cattle Egret/India/TN-02/2020, were recovered from 40 samples collected from egrets. The fusion protein gene  (F gene) was sequenced, and alignment analysis was performed between the two isolates and 59 other published NDVs of different  genotypes. The phylogenetic analysis based on nucleotide sequence including F gene cleavage site exactly positioned the isolates in  Genotype II of NDV. Deduced amino acids revealed the pattern 112 G-R-Q-G-R-L 117 at the cleavage site of the fusion protein. Thus,  egrets harbor genotype II virus, which could have been derived from the lentogenic strain used to vaccinate commercial poultry.
Keywords: Egret; F gene; Feral birds; Genotype; Newcastle Disease Virus; Peafowl